# Substitution help!!!!?

A=3 B= -1 C = -2 D=0 E=0

A(-B+1/C)=?

A^2(BC)^3+D/C=?

A - B^2 (C^3/A)=?

AEC^3 / (A^2B^3D)=?

Need proper breakdown, please :).

### 4 Answers

- 10 years agoFavorite Answer
All you do is, when you see a letter, you put the number that it equals in its place. I'll do the first one for you so you get how to do the rest.

A(-B+1/C)= First substitute the numbers in for the letters.

3(-(-1)+1/(-2))= You then want to solve what is in the parenthesis first, start by simplifying the top.

3(2/(-2))= Then finish solving the parenthesis

3(-1)= -3

Always remember to follow the order of operations, otherwise you'll get a wrong answer!

And that's why it's called substitution; it tells you that you need to substitute one thing for another, in this case we substitute numbers for letters.

- pygmalinLv 410 years ago
A=3 B= -1 C = -2 D=0 E=0

A(-B+1/C)=?

A^2(BC)^3+D/C=?

A - B^2 (C^3/A)=?

AEC^3 / (A^2B^3D)=?

3(+1+1/-2) OR 3(1-1/2) BECAUSE two negitives equal a positive

3^2(-1x-2)^3-2/0 2/0=0

You can figure out the rest. Remember to apply proper negitive and positive signs. And remember you solving equation rules.

- 10 years ago
wats so difficult..jus substitute the values..

1st one is .. 1.5 3(1-1/2) since -(-1)=1 nd 1/-2 is - 1/2

2nd one is 531441 .. 3^2(-1x-2)^3 + 0/-2 = 3^12 or 81^3 + 0. [ here i assumed only D/C nd not the whole thing coz u dint put them in brackets.

3rd one is 5.. 3 -[(-1)^2 x (-2)^3/3 ] do the brackets first u get -2 ther.. 3 --2 =5

4th one is 0.. coz ther is Ein the numerator nd its gettin multiplied so numberator becomes 0 nd 0 divided by any other number is 0... :)